P542Cardiac autonomic dysfunction and inflammatory response in heart failure - markers for cardiac resynchronization therapy response?. (18th June 2020) - Oliveira, S; Abreu, A; Cunha, P; Carmo, M M; Valente, B; Ricardo, I; Delgado, A S; Oliveira, L; Pinto, F; Oliveira, M M
Abstract: Funding Acknowledgements: FCP Introduction: Cardiac sympathetic activation and inflammatory response are involved in chronic heart failure (HF) pathophysiology. The severity of autonomic dysfunction and inflammation might be responsible for different responses to HF treatment. Aim: To evaluate the impact of cardiac autonomic dysfunction, and it´s association with systemic inflammation, on cardiac resynchronization therapy (CRT) response in severe HF patients. Methods: Single centre, prospective, longitudinal study, including consecutive patients, referred to CRT. Demographic data, HF aetiology and NYHA class were evaluated. Left ventricular (LV) function data (LV ejection fraction - LVEF) by echocardiography, heart to mediastinum early ratio (HMRe) by 123I-MIBG cardiac scintigraphy, and plasmatic TNF-α levels (pg/mL) were determined, at baseline and 4 months after CRT implantation. CRT response was defined by an absolute increase of at least 5% in LVEF at 4 months evaluation after CRT. Patients were divided in 4 groups according to HMRe and TNF-α cut-points: Group I (TNF-α > 2.0 pg/ml + HMRe ≥ 1.6), Group II (TNF-α > 2.0 pg/ml + HMRe < 1.6), Group III (TNF-α ≤ 2.0 pg/ml + HMRe ≥ 1.6) and Group IV (TNF-α ≤ 2.0 pg/ml + HMRe < 1.6). Data was analyzed using descriptive statistics and groups were compared by Fisher"s exact test. Results: A total of 95 patients were included (age 68.6 ± 10.2 years), 67.4% male and 32.6% female, 40% with diabetes mellitus, 30.5% with ischemic cardiomyopathy, 23.2% in NYHA III/IV, baseline LVEF - 26 ± 7%. At 4 months, LVEF was 40 ± 11%. In total, 73.7% were responders and 26.3% were non-responders to CRT. There were 28 patients (29.5%) with HMRe ≥ 1.6, with 25 responders (89.3%) and 48 patients (50.5%) with TNF-α ≤ 2.0 pg/ml, with 38 responders (79.2%). Group I had 16 patients (16.8%), with 81.2% responders; Group II had 31 patients (32.7%), with 61.3% responders; Group III had 12 patients (12.6%), with 100% responders, and Group IV had 36 patients (37.9%), with 72.2% responders. Conclusion: In patients with severe HF submitted to CRT, combining cardiac autonomic dysfunction and inflammation, associated to high rate of CRT non response. Contrarily, those with preserved cardiac autonomic function and no increased levels of inflammation identified most significantly CRT responders.